Effect of various ethanol/diesel cosolvents addition on combustion and emission characteristics of a CRDI heavy diesel engine. (November 2022) - Liang, Jichao; Zhang, Quanchang; Ma, Qixin; Chen, Zheng; Zheng, Zunqing
Abstract: Solubility between ethanol and diesel impedes the application of ethanol in diesel engines. The objective of the experiment is to compare combustion and emission characteristics of ethanol/diesel fuels using biodiesel, n-pentanol, tetrahydrofuran (THF) as cosolvents respectively on a diesel engine under variable engine loads, exhaust gas recirculation (EGR) rates, and injection timings. The results show: All tested blends increase the indicated thermal efficiency (ITE) except at low load, and THF/ethanol/diesel fuel exhibits a higher ITE. The Coefficient of Variations of Indicated Mean Effective Pressure (COV I M E P ) of ethanol/diesel blends is higher than that of diesel at low load. Under EGR conditions, ethanol/diesel blends run at lower COV I M E P, especially for biodiesel/ethanol/diesel fuel. At higher loads, all ethanol/diesel blends can decrease carbon monoxide (CO) emissions, especially for THF/ethanol/diesel fuel. Excessive retard of injection timing will increase CO and total hydrocarbon (THC) emissions of ethanol/diesel fuels. The soot emissions of THF/ethanol/diesel fuel are lower than those of n-pentanol/ethanol/diesel fuel under higher EGR rates. The effect of injection timing on soot emissions becomes more pronounced at slightly higher EGR rates. Compared to diesel, biodiesel/ethanol/diesel fuel increases nitrogen oxide (NO x ) emissions, especially at medium-low load, whereas n-pentanol/ethanol/diesel and THF/ethanol/diesel fuels reduce NO x at low and high loads, slightly increase NO x emissions at medium loads. In conclusion, THF may be a more promising ethanol/diesel cosolvent compared with high alcohols and biodiesel in terms of fuel economy and emissions, especially under EGR and heavy load conditions. Highlights: THF possesses a better ability to dissolve ethanol/diesel than n-pentanol and biodiesel. The ITE of the THF/ethanol/diesel fuels increases in contrast with the diesel fuel under. The cycle-to-cycle combustion variation of different ethanol/diesel blends was investigated. The injection timing effects on emissions of three ternary ethanol/diesel blends were reported at different EGR rates.